A comparison of the rate of retraction with low-level laser therapy and conventional retraction technique - Saran Arumughan; Sanju Somaiah; Sunil Muddaiah; Balakrishna Shetty; Goutham Reddy; S Roopa (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: A major concern of orthodontic patients is treatment time. Reducing the treatment time requires increasing the rate of orthodontic tooth movement. Research has proved that bone resorption is the rate-limiting step in tooth movement. Therefore, any procedure that potentiates osteoclastic activity is capable of increasing the rate of orthodontic tooth movement. Low-level laser has been indicated to have the capability to facilitate the differentiation of the osteoclastic and osteoblastic cells, which are responsible for the bone remodeling process. The purpose of this study was to evaluate whether the low-level laser therapy can accelerate orthodontic tooth movement during en masse retraction. Method: The study was a split-mouth design. The experimental side was exposed to biostimulation using 810 nm gallium-aluminium-arsenide diode laser. A total of 10 irradiations for 10 s per site were given 5 on the buccal side and 5 on the palatal side of the tooth. The total energy density at each application was 10 J with an interappointment gap of 3 weeks. The retraction was carried using a constant force of 150 gm. A digital vernier caliper measurement was used to measure the distance between the contact points of the maxillary canine and second premolar on 1st and 84th day. Results: The rate of orthodontic tooth movement was faster on the experimental side, and the difference between the two sides was statistically significant (P < 0.014). Interpretation and Conclusion: It was concluded that biostimulation carried out using an 810 nm diode laser is capable of increasing the rate of extraction space closure. Hence, it is capable of increasing the rate of orthodontic tooth movement.